Psychoacoustic Characteristics of Tinnitus in Relation to Audiometric Profile - RISTOVSKA, Lidija; JACHOVA, Zora; STOJCHESKA, Vase (Archives of Acoustics, 2019)
The aim of the study was to examine the relationship between tinnitus pitch and maximum hearing loss, frequency range of hearing loss, and the edge frequency of the audiogram, as well as, to analyze tinnitus loudness at tinnitus frequency and normal hearing frequency.The study included 212 patients, aged between 21 to 75 years (mean age of 54.4 ±13.5 years) with chronic subjective tinnitus and sensorineural hearing loss. For the statistical data analysis we used Chi-square test and Fisher’s exact test with level of significance p < 0.05. Tinnitus pitch corresponding to the frequency range of hearing loss, maximum hearing loss and the edge frequency was found in 70.8%, 37.3%, and 16.5% of the patients, respectively. The majority of patients had tinnitus pitch from 3000 to 8000 Hz corresponding to the range of hearing loss (p < 0.001). The mean tinnitus pitch was 3545 Hz ±2482. The majority (66%) of patients had tinnitus loudness 4–7 dB SL. The mean sensation level at tinnitus frequency was 4.9 dB SL ±1.9, and 13 dB SL ±2.9 at normal hearing frequency. Tinnitus pitch corresponded to the frequency range of hearing loss in majority of patients. There was no relationship between tinnitus pitch and the edge frequency of the audiogram. Loudness matching outside the tinnitus frequency showed higher sensation level than loudness matching at tinnitus frequency.